Evaluation of a new automated pulmonary gas analysis system - Hallenstål, T.; Sundqvist, I.; Svensson, M.; Yu, J.-G. (International Journal of Exercise Science, 2015)
The study aimed to evaluate the validity and reliability of a new automated pulmonary gas analysis system - Exercise Physiology System (EPS). The Oxycon Pro, a well-established automated pulmonary gas analysis system was used as a reference system. Six well-trained cyclists were recruited and performed two identical submaximal exercises on a cycle ergometer over one week interval. During the exercises, pulmonary gas exchange: ventilation (VE), oxygen consumption (VO2), elimination of carbon dioxide (VCO2), and ratio between carbon dioxide and oxygen (RER) was measured using both systems in randomized order. The exercise was composed of three incremental work-loads (Watt) of low, medium, and high load corresponding to 40%, 60%, and 80% of individual maximal work-load. Each work-load was performed twice so that pulmonary gas exchange was analyzed twice on each work-load using both systems. EPS validity was assessed by comparing the measurements from the two systems. For measurements presenting agreement between the systems, Bland-Altman plot analysis was performed to identify outlier. Reliability was evaluated by comparisons of measurements from repeated tests through each system, and by calculations of intra-class correlation coefficient (ICC) and standard error of measurement (SEM). Validity evaluations revealed that the majority of the measurements were in disagreements between the systems and most of them appeared at lower work-loads. The results indicated that at lower work-loads, EPS had lower validity than Oxycon Pro. At higher work-loads, ESP had high and comparable validity with Oxycon Pro. Reliability assessments revealed that agreements between repeated tests appeared in almost all measurements through both systems. Excellent agreements (very high ICC) in measurements between repeated tests were observed in VE, VO2, and VCO2 from both systems, and very small measurement errors (SEM), close to zero were observed in VO2, VCO2, and RER. The results suggested that the two systems had high and comparable reliability in measurement of pulmonary gas exchange.